Pole piece, manufacturing method, and battery

CN120565573BActive Publication Date: 2026-10-27JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510502630.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-21
Publication Date
2026-10-27
Estimated Expiration
2045-04-21

AI Technical Summary

Technical Problem

随着对电池能量密度和使用环境要求的提高,高能量密度的三元正极材料被广泛使用,但三元正极材料释放的热量及热失控风险远高于其他体系电池

Benefits of technology

[0046]本发明实施例中,所提供的极片,在集流体上设置第一活性物质层、第二活性物质层以及保护层,保护层包括硅橡胶和添加剂;通过设置含有硅橡胶的保护层,能够有效降低电池发生热失控的风险,提升电池的化学稳定性与热稳定性,进而提升电池的循环性能与安全性能,同时保护层还具有较高的抗张强度,能够提升极片的柔韧性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005369093450000171
    Figure BDA0005369093450000171
Patent Text Reader

Abstract

The application belongs to the technical field of batteries, and particularly relates to a pole piece, a preparation method and a battery. The disclosed pole piece comprises a current collector, a first active material layer, a second active material layer and a protective layer; the first active material layer is arranged on at least one surface of the current collector, and the first active material layer comprises a first active material; the second active material layer is arranged on a surface of the first active material layer away from the current collector, and the second active material layer comprises a second active material; and the protective layer is arranged on a surface of the second active material layer away from the first active material layer, and the protective layer comprises silicone rubber and an additive. The application can effectively reduce the risk of thermal runaway of the battery, and improve the stability and flame retardant performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery technology, specifically relating to an electrode, a preparation method, and a battery. Background Technology

[0002] As a key technology for new energy vehicles, the performance and safety of lithium-ion batteries are of paramount importance. With increasing demands for battery energy density and operating environment, high-energy-density ternary cathode materials are widely used. However, the heat released and the risk of thermal runaway from ternary cathode materials are far higher than those of other battery systems.

[0003] Therefore, it is crucial to obtain an electrode with electrochemical stability and flame retardancy to enhance the cycle performance and safety performance of the battery. Summary of the Invention

[0004] In view of this, the present invention aims to at least partially solve one of the technical problems in the related art. The present invention provides an electrode, a preparation method, and a battery, which can effectively reduce the risk of battery thermal runaway and improve the battery's stability and flame retardant performance.

[0005] According to a first aspect of the present invention, an electrode sheet is provided, comprising:

[0006] current collector;

[0007] A first active material layer is disposed on at least one surface of the current collector, and the first active material layer includes a first active material.

[0008] A second active material layer is disposed on the surface of the first active material layer away from the current collector, and the second active material layer includes a second active material.

[0009] A protective layer is disposed on the surface of the second active material layer away from the first active material layer, and the protective layer comprises silicone rubber and additives.

[0010] In one optional embodiment, the protective layer comprises the following components in parts by weight: 100 parts silicone rubber and 86.5 to 97 parts additives.

[0011] In one optional implementation, the additive includes a flame retardant, a reinforcing agent, and a vulcanizing agent, and the mass of each of the flame retardant, reinforcing agent, and vulcanizing agent is not zero.

[0012] In one optional embodiment, the protective layer comprises the following components in parts by weight: 100 parts silicone rubber, 45-50 parts reinforcing agent, 40-45 parts flame retardant, and 1.5-2 parts vulcanizing agent.

[0013] In one alternative embodiment, the protective layer satisfies at least one of features (1) to (3): (1) the flame retardant includes at least one of aluminum hydroxide or magnesium hydroxide; (2) the reinforcing agent includes fumed silica; and (3) the vulcanizing agent includes bis(2,4)-dichlorosulfurizing agent.

[0014] In one optional implementation, the first active material and the second active material are positive electrode active materials.

[0015] In one optional implementation, the positive electrode active material includes at least one of ternary materials, lithium iron phosphate, or lithium manganese iron phosphate.

[0016] In one optional embodiment, the first active material comprises a ternary material A; preferably, the ternary material A comprises LiNi. x Co y Mn 1-x-y O2 or LiNi x Co y Al 1-x-y At least one of O2; wherein x ≥ 0.8, 0.05 ≤ y ≤ 0.2.

[0017] In one optional implementation, the ternary material A comprises primary particles;

[0018] In one optional embodiment, the second active material comprises ternary material B; preferably, the ternary material B comprises LiNi. x Co y Mn 1-x-y O2 or LiNi x Co y Al 1-x-y At least one of O2; wherein x ≥ 0.8, 0.05 ≤ y ≤ 0.2.

[0019] In one alternative implementation, the ternary material B comprises secondary particles.

[0020] In one optional implementation, both the first active material and the second active material contain nickel, and the nickel content in the first active material is different from that in the second active material.

[0021] In one optional implementation, the first active material and the second active material are negative electrode active materials.

[0022] In one optional embodiment, the first active material includes at least one of silicon-based materials and carbon-based materials; the first active material includes primary particles; the second active material includes at least one of silicon-based materials and carbon-based materials; the second active material includes secondary particles.

[0023] In one optional implementation, the thickness of the protective layer is 3 μm to 10 μm.

[0024] In one optional implementation, the areal density of the protective layer is 15 mg / m³. 2 ~30mg / m 2 .

[0025] In one alternative implementation, the mass percentage of the first active material is 95% to 97% based on the mass of the first active material layer.

[0026] In one alternative embodiment, the first active material layer further includes a first conductive agent and a first binder.

[0027] In one alternative implementation, the mass percentage of the first conductive agent is 1% to 1.5% based on the mass of the first active material layer.

[0028] In one alternative implementation, the mass percentage of the first adhesive is 2% to 3.5% based on the mass of the first active material layer.

[0029] In one alternative implementation, the first conductive agent includes one or more of conductive carbon black, vapor-generated carbon fiber, graphene, or carbon nanotubes.

[0030] In one optional implementation, the mass percentage of the second active material is 95% to 97%, based on the mass of the second active material layer.

[0031] In one alternative embodiment, the second active material layer further includes a second conductive agent and a second binder.

[0032] In one alternative implementation, the mass percentage of the second conductive agent is 1% to 1.5% based on the mass of the second active material layer.

[0033] In one alternative implementation, the mass percentage of the second adhesive is 2% to 3.5% based on the mass of the second active material layer.

[0034] In one alternative embodiment, the second conductive agent includes one or more of conductive carbon black, vapor-generated carbon fibers, graphene, or carbon nanotubes.

[0035] According to a second aspect of the present invention, the present invention provides a method for preparing an electrode sheet, comprising the following steps:

[0036] A first slurry is coated on at least one side of the current collector to obtain a first active material layer;

[0037] A second slurry is coated on the surface of the first active material layer to obtain a second active material layer;

[0038] A protective slurry is coated onto the surface of the second active material layer to obtain a protective layer.

[0039] The first active material layer includes a first active material; the second active material layer includes a second active material; and the protective layer includes silicone rubber and additives.

[0040] In one optional implementation, the step of obtaining the protective layer specifically includes:

[0041] The silicone rubber and additives are mixed evenly to obtain a protective slurry; preferably, the silicone rubber, flame retardant, reinforcing agent and vulcanizing agent are mixed evenly to obtain a protective slurry.

[0042] The protective slurry is coated onto the surface of the second active material layer. The coating thickness is 10 μm to 40 μm. After drying, the protective layer is obtained.

[0043] According to a third aspect of the present invention, the present invention also provides a battery comprising: a separator, an electrolyte, and an electrode as described in any embodiment of the first aspect of the present invention.

[0044] In one alternative embodiment, the battery further includes an electrode sheet prepared by the preparation method described in any embodiment of the second aspect of the present invention.

[0045] The electrode, preparation method, and battery provided by this invention also have the following beneficial effects:

[0046] In this embodiment of the invention, the provided electrode sheet has a first active material layer, a second active material layer, and a protective layer on the current collector. The protective layer includes silicone rubber and additives. By setting a protective layer containing silicone rubber, the risk of thermal runaway of the battery can be effectively reduced, the chemical stability and thermal stability of the battery can be improved, and the cycle performance and safety performance of the battery can be improved. At the same time, the protective layer also has high tensile strength, which can improve the flexibility of the electrode sheet.

[0047] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Detailed Implementation

[0048] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.

[0049] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges or individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0050] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.

[0051] Unless otherwise specified, all technical features and optional technical features of this invention can be combined to form new technical solutions.

[0052] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0053] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0054] To improve the energy density of lithium-ion batteries, ternary materials are typically used. However, the high energy density of ternary materials comes with higher safety risks for lithium-ion batteries. For example, the high heat release of ternary materials increases the risk of thermal runaway, which can lead to problems such as fires.

[0055] In view of the above-mentioned problems, the present invention provides an electrode, a preparation method and a battery, which can effectively reduce the risk of battery thermal runaway and improve the stability and flame retardant performance of the battery.

[0056] The technical solution provided by this invention is as follows:

[0057] [Extreme Film]

[0058] In some embodiments, an electrode is provided, the electrode comprising: a current collector, a first active material layer, and a second active material layer; the first active material layer is disposed on at least one surface of the current collector, and the first active material layer comprises a first active material; the second active material layer is disposed on the surface of the first active material layer away from the current collector, and the second active material layer comprises a second active material.

[0059] In this application, the current collector includes, but is not limited to, any one of homogeneous aluminum foil, porous aluminum foil, aluminum foil with a carbon coating, copper foil, or aluminum alloy foil. In the thickness direction, a first active material layer is disposed on one or both surfaces of the current collector, and a second active material layer is disposed on the first active material layer. As an example, the current collector has two surfaces opposite each other in its own thickness direction, the first active material layer is disposed on the two opposite surfaces of the current collector, and a second active material layer is further disposed on the surface of the first active material layer. It is understood that in other embodiments, the first active material layer may also be formed on either of the two surfaces of the current collector. Here, "surface" can refer to the entire area of ​​the current collector or a portion of the current collector; this application does not have a particular limitation in this regard, as long as the purpose of this application is achieved.

[0060] In this embodiment of the invention, the electrode can be applied in the cell structure of a battery. Specifically, the electrode can be a positive electrode or a negative electrode. That is, the polarity of the electrode can be positive or negative. In particular, based on the existing requirements for improved fast charging and energy density, as well as the requirements for chemical and thermal stability, the electrode is more preferred as a positive electrode.

[0061] For example, in some embodiments, the electrode is a positive electrode. When the electrode is a positive electrode, both the first active material layer and the second active material layer include positive active material.

[0062] As an example, the first active material layer includes a first active material, and the second active material layer includes a second active material; the first and second active materials may be, but are not limited to, ternary materials, lithium iron phosphate, or lithium manganese iron phosphate, etc., as positive electrode active materials. Exemplarily, the first active material may be selected from ternary materials with high energy density, such as NCM (LiNi). x Co y Mn x O2) or NCA (LiNi) x Co y Al z One or more of the following (O2), specifically NCM811 or NCM532, etc.; the second active substance may be selected from one or more of NCM811, NCM532 or NCA.

[0063] The selection of the first and second active materials can differ, for example, in terms of crystal structure, particle size, nickel content, or cobalt content. For instance, the first and second active materials may have different crystal structures: the first active material is a single-crystal material, while the second active material is a polycrystalline material. This enhances the structural stability of the electrode. Because the first active material is a single-crystal material, it possesses better structural stability due to the absence of internal grain boundaries, reducing microcrack formation during charge and discharge, thus improving cycle stability. Furthermore, since the first active material is located in the first active material layer near the current collector, the single-crystal material provides better thermal stability in the lower layers, reducing the risk of thermal runaway; while the polycrystalline material in the second active material layer, farther from the current collector, provides better electrochemical activity. Simultaneously, the single-crystal first active material layer reduces side reactions with the electrolyte, improving battery safety and lifespan.

[0064] For example, the first active material in the first active material layer near the current collector is a polycrystalline material, and the second active material in the second active material layer away from the current collector is a monocrystalline material. Polycrystalline materials generally have higher electrical conductivity, and placing polycrystalline materials at the bottom layer can improve the overall conductivity of the electrode, thereby improving the rate performance of the battery. At the same time, the polycrystalline material at the bottom layer helps to reduce battery polarization, increase the median voltage during rate discharge, and reduce side reactions during battery storage; due to its higher electrical conductivity and larger specific surface area, polycrystalline materials can improve the rate performance of the battery.

[0065] Of course, the materials in the first and second active materials can have different nickel content. By superimposing the nickel content in the two active material layers, a synergistic effect can be achieved, further improving the battery capacity.

[0066] In some embodiments, the electrode further includes a protective layer disposed on the surface of the second active material layer away from the first active material layer, the protective layer comprising silicone rubber and additives.

[0067] To avoid the risk of thermal runaway during fast charging and other processes, a protective layer is also provided on the surface of the second active material layer, forming an electrode with a structure consisting of a current collector, a first active material layer, a second active material layer, and a protective layer in sequence. That is, the electrode includes a current collector, a first active material layer, a second active material layer, and a protective layer stacked in sequence.

[0068] The protective layer includes silicone rubber, the raw silicone rubber of which can be one or more of methyl silicone rubber, methyl vinyl silicone rubber, methyl phenyl vinyl silicone rubber, or fluorosilicone rubber. Silicone rubber is obtained by cross-linking the raw rubber with a vulcanizing agent. Of course, to improve the cross-linking of the silicone rubber, additives such as silica and alumina can be added to the raw silicone rubber, greatly enhancing its high-temperature resistance and mechanical properties.

[0069] By setting this protective layer, the battery can be guaranteed to have high energy density and excellent safety performance. The protective layer can improve the high temperature resistance of the electrode and avoid the risk of thermal runaway, fire and other risks caused by the sudden generation of high heat. The protective layer containing silicone rubber can also improve the mechanical properties and cycle stability of the electrode to a certain extent.

[0070] Therefore, the electrode of this application not only has a layered active material layer, but also a protective layer. This layered design can simultaneously consider energy density and kinetic performance; the protective layer on the outermost side of the electrode improves its chemical and thermal stability, thereby enhancing the battery's cycle performance and safety. Simultaneously, the high tensile strength of the first and second active material layers improves the electrode's flexibility. For example, one of the first and second active material layers can be a monocrystalline layer, and the other a polycrystalline layer; using a monocrystalline layer improves cycle performance, while using a polycrystalline layer improves energy density.

[0071] In some embodiments, the protective layer comprises the following components in parts by weight: 100 parts silicone rubber and 86.5 to 97 parts additives.

[0072] Specifically, the mass fraction of silicone rubber is 100 parts, and the mass fraction of additives can be 86.5 parts, 87 parts, 88 parts, 89 parts, 90 parts, 91 parts, 92 parts, 93 parts, 94 parts, 95 parts, 96 parts, or 97 parts. Limiting the mass fraction range of silicone rubber and additives can improve the crosslinking degree of silicone rubber to a certain extent, thereby improving the mechanical properties of the protective layer and enabling the electrode to have good flexibility and high temperature resistance.

[0073] In some embodiments, the additives include flame retardants, reinforcing agents, and vulcanizing agents, and the mass of each of the flame retardant, reinforcing agent, and vulcanizing agent is not 0; preferably, the protective layer comprises the following components in parts by mass: 100 parts silicone rubber, 45-50 parts reinforcing agent, 40-45 parts flame retardant, and 1.5-2 parts vulcanizing agent.

[0074] The reinforcing agents include, but are not limited to, sepiolite, zinc oxide, magnesium oxide, or carbon black, with fumed silica being a preferred reinforcing agent. The weight percentage of the reinforcing agent can be 45, 46, 47, 48, 49, or 50 parts. The flame retardants include, but are not limited to, magnesium hydroxide, aluminum hydroxide, or ammonium phosphate, and the weight percentage of the flame retardants can be 45, 46, 47, 48, 49, or 50 parts. The vulcanizing agents include, but are not limited to, sulfur monochloride or sulfur, and the weight percentage of the vulcanizing agents can be 1.5, 1.6, 1.7, 1.8, 1.9, or 2.0 parts. The flame retardants enable the protective layer to have flame-retardant properties, effectively preventing fires during battery thermal runaway. The reinforcing agents effectively improve the strength and high-temperature resistance of the protective layer, further enhancing battery safety. The vulcanizing agents enable the silicone rubber to form a complex three-dimensional network structure, improving the physical and mechanical properties of the silicone rubber.

[0075] In some preferred embodiments, the flame retardant in the protective layer includes at least one of aluminum hydroxide or magnesium hydroxide.

[0076] Aluminum hydroxide or magnesium hydroxide, as flame retardants, decompose into oxides and water at high temperatures when a battery experiences thermal runaway. This lowers the temperature at the combustion site, and the generated water converts into water vapor, effectively isolating oxygen and thus providing a flame-retardant effect. Furthermore, the relatively low decomposition temperatures of magnesium hydroxide and aluminum hydroxide make the protective layer more sensitive, allowing it to act as a flame retardant in the early stages of thermal runaway, preventing its further spread. Additionally, the flame-retardant properties of aluminum hydroxide may allow it to participate in the formation of a cross-linked network in silicone rubber, improving the heat and chemical resistance of the protective layer.

[0077] In some preferred embodiments, the reinforcing agent in the protective layer includes fumed silica.

[0078] Fumed silica was chosen as the reinforcing agent because of its excellent dispersibility. When mixed with silicone rubber, it can be uniformly dispersed within the silicone rubber. Furthermore, the large specific surface area and surface adsorption capacity of fumed silica can further enhance the strength of the silicone rubber. The microporous structure of fumed silica helps improve the physical strength and abrasion resistance of silicone rubber, further extending the service life of the protective layer.

[0079] In some preferred embodiments, the vulcanizing agent in the protective layer includes a bis(2,4)-2,4-disulfide agent.

[0080] The bis(2,4) curing agent can promote cross-linking between rubber molecules in the vulcanization process of silicone rubber, improve the thermal stability, mechanical strength and aging resistance of the protective layer; and a good cross-linking network helps maintain the structural integrity of the material.

[0081] In some preferred embodiments, the protective layer comprises the following components in parts by weight: 100 parts silicone rubber, 45-50 parts fumed silica, 40-45 parts aluminum hydroxide, and 1.5-2 parts bis(2,4)-tetrachlorohydrin.

[0082] By setting the above protective layer, the electrode can simultaneously possess electrochemical stability and flame retardancy, thereby enhancing the cycle performance and safety performance of the battery.

[0083] In some embodiments, the electrode is a positive electrode, and the first active material and the second active material are positive electrode active materials. When the electrode is a positive electrode, the above-mentioned protective layer can also be called an artificial CEI film, which can enable the electrode to simultaneously possess electrochemical stability and flame retardancy, thereby enhancing the cycle performance and safety performance of the battery.

[0084] If the electrode is a positive electrode, the positive electrode active material includes, but is not limited to, ternary materials, lithium iron phosphate, or lithium manganese iron phosphate; the first active material and the second active material can be the same for the positive electrode active material, or preferably different, forming a gradient between the first active material layer and the second active material layer, which can improve the battery capacity and cycle rate.

[0085] In some embodiments, the first active material includes ternary material A; preferably, ternary material A includes LiNi. x Co y Mn 1-x-y O2 or LiNi x Co y Al 1-x-y At least one of O2; wherein x ≥ 0.8, 0.05 ≤ y ≤ 0.2.

[0086] Ternary material A includes, but is not limited to, LiNi 0.8 Co 0.05 Mn 0.15 O2, LiNi 0.85 Co 0.05 Mn 0.15 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.92 Co 0.05 Mn 0.03 O2, LiNi 0.8 Co 0.05 Al 0.15 O2, LiNi 0.8 Co 0.2 O2, LiNi 0.9 Co 0.1 Al 0.1 O2 or LiNi 0.85 Co 0.05Al 0.1 The value is any one of the values ​​in O2 or any point within the range of either x or y. Ternary material A is selected from ternary materials with high nickel content, which can ensure that the battery has high energy density and cycle performance.

[0087] In some embodiments, ternary material A comprises primary particles;

[0088] By limiting ternary material A to primary particles, ternary material A has good structural stability. Its grains will not break at high temperatures, and it has good cycle stability, thus improving the safety performance of the battery.

[0089] In some embodiments, the second active material includes ternary material B; preferably, ternary material B includes LiNi. x Co y Mn 1-x-y O2 or LiNi x Co y Al 1-x-y At least one of O2; wherein x ≥ 0.8, 0.05 ≤ y ≤ 0.2.

[0090] Ternary materials B include, but are not limited to, LiNi 0.8 Co 0.05 Mn 0.15 O2, LiNi 0.85 Co 0.05 Mn 0.15 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.92 Co 0.05 Mn 0.03 O2, LiNi 0.8 Co 0.05 Al 0.15 O2, LiNi 0.8 Co 0.2 O2, LiNi 0.9 Co 0.1 Al 0.1 O2 or LiNi 0.85 Co 0.05 Al 0.1 The value is any one of the values ​​in O2 or any point within the range of either x or y. Ternary material B is selected from high-nickel ternary materials, ensuring the battery has high energy density and good cycle performance.

[0091] In some embodiments, ternary material B comprises secondary particles.

[0092] By limiting the ternary material B to secondary particles, the second active material layer can have a high compaction density, thereby improving the energy density of the battery. It also gives the second active material layer good mechanical strength and toughness, which can effectively control the particle size of the ternary material B and allow it to form a particle gradation, thereby improving the battery capacity and cycle performance.

[0093] Alternatively, in some embodiments, ternary material A comprises secondary particles, and ternary material B comprises primary particles.

[0094] In this application, ternary material A and ternary material B preferably employ different crystal structures or particle sizes. For example, ternary material A may include primary particles, and ternary material B may include secondary particles; or ternary material A may include secondary particles, and ternary material B may include primary particles. Alternatively, ternary material A may include a single-crystal material, and ternary material B may include a polycrystalline material; or ternary material A may include a polycrystalline material, and ternary material B may include a single-crystal material.

[0095] In some embodiments, both the first active substance and the second active substance contain nickel, and the nickel content in the first active substance is different from that in the second active substance.

[0096] By setting different nickel content in the first active material and the second active material, a nickel content gradient is created between the first and second active material layers. The two active material layers work synergistically to improve the battery's safety performance and capacity.

[0097] In some embodiments, the electrode is a negative electrode, and the first active material and the second active material are negative electrode active materials.

[0098] The electrode sheet of this application can also be a negative electrode sheet. Therefore, the first active material and the second active material mentioned above can both be negative electrode active materials to obtain a negative electrode sheet. The negative electrode active materials include, but are not limited to, one or more of graphite, hard carbon, soft carbon, molybdenum trioxide or carbon nanotubes.

[0099] In some embodiments, the first active material includes at least one of silicon-based materials and carbon-based materials; the first active material includes primary particles; the second active material includes at least one of silicon-based materials and carbon-based materials; the second active material includes secondary particles.

[0100] Alternatively, in some embodiments, the first active material comprises secondary particles; the second active material comprises primary particles.

[0101] Artificial graphite, natural graphite, or graphene in carbon-based materials, and silicon dioxide or molybdenum trioxide in silicon-based materials can all be used as the first and second active materials. At the same time, the first active material includes primary particles, and the second active material includes secondary particles. The first active material layer near the current collector has a more stable structure, and the second active material layer has a higher compaction density, thereby enabling the battery to have excellent safety performance and high energy density.

[0102] In some embodiments, the thickness of the protective layer is 3 μm to 10 μm.

[0103] Specifically, the thickness of the protective layer can be any one of 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, or 10μm, or any value between any two. By limiting the thickness of the protective layer, the safety performance can be better guaranteed, while ensuring that the cost is not too high; if it is higher than this range, it will be wasteful and significantly increase the cost, while if it is too low, it will not provide safety and flame retardant effects.

[0104] In some embodiments, the areal density of the protective layer is 15 mg / m³. 2 ~30mg / m 2 .

[0105] Specifically, the areal density of the protective layer can be 15 mg / m³. 2 16mg / m 2 17mg / m 2 18mg / m 2 19mg / m 2 20mg / m 2 24mg / m 2 26mg / m 2 Or 30mg / m 2 The value can be any one of the values ​​or any two of the values. By limiting the areal density of the protective layer, it is possible to ensure that lithium ions can shuttle through the protective layer, thereby ensuring the cycle rate performance of the battery. If the density is too high, it will hinder the shuttle of lithium ions and reduce the rate performance of the battery; if it is too low, it will not provide any protection.

[0106] In some embodiments, the mass percentage of the first active material is 95% to 97% based on the mass of the first active material layer.

[0107] The mass percentage of the first active material in the first active material layer can be any one of 95%, 96%, or 97%. Optionally, the first active material layer may also include a binder or the like to promote dense adhesion of the first active material.

[0108] In some embodiments, the first active material layer further includes a first conductive agent and a first binder; preferably, the mass percentage of the first conductive agent is 1% to 1.5% based on the mass of the first active material layer; preferably, the mass percentage of the first binder is 2% to 3.5% based on the mass of the first active material layer.

[0109] As an example, the mass percentage of the first conductive agent can be any one of 1%, 1.2%, or 1.5%, or any value between any two; the mass percentage of the first adhesive can be any one of 2%, 2.5%, 3%, 3.2%, or 3.5%, or any value between any two.

[0110] The first conductive agent includes, but is not limited to, one or more of conductive carbon black, vapor-generated carbon fiber, graphene, or carbon nanotubes; the first binder includes, but is not limited to, one or more of sodium carboxymethyl cellulose, polyvinylidene fluoride, or styrene-butadiene rubber.

[0111] In some embodiments, the mass percentage of the second active material is 95% to 97% based on the mass of the second active material layer.

[0112] The mass percentage of the second active material in the second active material layer can be any one of 95%, 96%, or 97%. Optionally, the second active material layer may also include a binder or the like to promote dense adhesion of the second active material.

[0113] In some embodiments, the second active material layer further includes a second conductive agent and a second binder; preferably, the mass percentage of the second conductive agent is 1% to 1.5% based on the mass of the second active material layer; preferably, the mass percentage of the second binder is 2% to 3.5% based on the mass of the second active material layer; preferably, the second conductive agent includes one or more of conductive carbon black, vapor-generated carbon fiber, graphene, or carbon nanotubes.

[0114] The mass percentage of the second conductive agent can be any one of 1%, 1.2%, or 1.5%, or any value between any two; the mass percentage of the second adhesive can be any one of 2%, 2.5%, 3%, 3.2%, or 3.5%, or any value between any two.

[0115] The second conductive agent includes, but is not limited to, one or more of conductive carbon black, vapor-generated carbon fiber, graphene, or carbon nanotubes; the second binder includes, but is not limited to, one or more of sodium carboxymethyl cellulose, polyvinylidene fluoride, or styrene-butadiene rubber.

[0116] [Preparation methods for electrode sheets]

[0117] This invention also provides a method for preparing an electrode, comprising the following steps:

[0118] S101. A first slurry is coated on at least one side of the current collector to obtain a first active material layer.

[0119] A first slurry is coated onto one or both surfaces of the current collector to obtain a first active material layer. The first slurry includes a first active material, a first binder, and a first conductive agent.

[0120] S102. Coat the surface of the first active material layer with a second slurry to obtain the second active material layer.

[0121] The second slurry includes a second active material, and the second slurry also includes a second binder and a second conductive agent; the obtained second slurry is coated on the first active material layer to obtain the second active material layer.

[0122] S103. A protective slurry is coated on the surface of the second active material layer to obtain a protective layer.

[0123] The protective slurry includes silicone rubber and additives. The uniformly mixed protective slurry is coated onto the second active material layer to obtain a protective layer.

[0124] In some embodiments, the step of obtaining the protective layer specifically includes:

[0125] S201. The silicone rubber and additives are mixed evenly to obtain a protective slurry; preferably, the silicone rubber, flame retardant, reinforcing agent and vulcanizing agent are mixed evenly to obtain a protective slurry.

[0126] Silicone rubber, flame retardant, reinforcing agent and vulcanizing agent are added to a mixer or open mill for mixing. Those skilled in the art will understand that the temperature and time for mixing using an open mill or mixer can be selected based on the present invention, and no specific limitation is made here.

[0127] S202. A protective slurry is coated onto the surface of the second active material layer. The coating thickness is 10 μm to 40 μm. After drying, a protective layer is obtained. Preferably, the coating thickness is 20 μm to 30 μm.

[0128] The prepared protective slurry is applied to the surface of the second active material layer by a doctor blade coating method. The doctor blade thickness can be any one of 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, or 40μm, or any value between any two. Limiting the thickness of the doctor blade coating ensures the thickness of the subsequent protective layer. An excessively thick protective layer would increase costs and potentially reduce the thickness of the active material layer within the limited space of the battery, thus affecting the battery capacity. Conversely, an excessively thin protective layer would fail to effectively reduce the risk of thermal runaway.

[0129] Optionally, in step S202, the drying is carried out in a forced-air drying oven at 80℃~100℃ for 8h~12h.

[0130] [Battery]

[0131] The present invention also provides a battery comprising: a separator, an electrolyte, and an electrode as described in any of the above embodiments of the present invention.

[0132] If both the first and second active materials are positive electrode active materials, then the electrode is a positive electrode; if both the first and second active materials are negative electrode active materials, then the electrode is a negative electrode.

[0133] The battery may consist of only a negative electrode, only a positive electrode, or both a positive and a negative electrode.

[0134] In some embodiments, the battery further includes an electrode prepared by the electrode preparation method in any of the above embodiments of the present invention.

[0135] The battery also includes a separator and an electrolyte. The separator can be any one of polypropylene (PP), polyethylene (PE), polyimide (PI), or polypropylene / polyethylene composite (PP / PE). The lithium salt of the electrolyte is lithium hexafluorophosphate (LiPF6), and the solvent includes cyclic carbonates (EC) and chain carbonates such as dimethyl carbonate (DMC) / ethyl methyl carbonate (EMC) / diethyl carbonate (DEC).

[0136] Since the battery provided in this embodiment of the invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, which will not be repeated here.

[0137] The present application will be described in detail below with reference to embodiments and comparative examples, but the implementation and protection of the present invention are not limited thereto. The following embodiments are only some embodiments of the present application and are not intended to limit the present application.

[0138] 1. Preparation of positive electrode sheet

[0139] (1) Preparation of the first active material layer: The first active material includes LiNi 0.8 Co 0.05 Mn 0.15 O2 ternary high-nickel single crystal material, conductive agent, and binder are mixed uniformly at a mass ratio of 97:2:1. The conductive agent is selected from SP (conductive carbon black) and oily single-walled carbon nanotubes. The positive electrode binder is selected from PVDF (polyvinylidene fluoride) mixed with NMP (N-methylpyrrolidone) and stirred to form a uniform and stable first slurry. The first slurry is uniformly coated on the positive electrode current collector with a coating surface density of 155 g / m². 2The compacted density is 3.45 g / cm³. 3 .

[0140] (2) Preparation of the second active material layer: The first active material includes LiNi 0.8 Co 0.05 Mn 0.15 O2 ternary high-nickel polycrystalline material, conductive agent, and binder are mixed uniformly at a mass ratio of 97:2:1. The conductive agent is selected from SP (conductive carbon black) and oily single-walled carbon nanotubes. The positive electrode binder is selected from PVDF (polyvinylidene fluoride) mixed with NMP (N-methylpyrrolidone) and stirred to form a uniform and stable second slurry. The second slurry is uniformly coated on the first active material layer, with a coating surface density of 155 g / m². 2 The compacted density is 3.45 g / cm³. 3 .

[0141] (3) Preparation of protective layer: 100 parts by weight of silicone rubber, 45-50 parts by weight of fumed silica, 40-45 parts by weight of aluminum hydroxide, and 1.5-2 parts by weight of bis(2,4)-tetrachlorohydrin are mixed with a high-speed mixer for 30 minutes to form a uniform slurry. The slurry is then coated on the surface of the second active material layer with a thickness of 20 μm. Finally, it is dried in an 80°C forced-air drying oven for more than 8 hours.

[0142] 2. Preparation of the negative electrode sheet: Graphite is selected as the active material, SP and carbon nanotubes are selected as the conductive agent, PAA (polyacrylic acid) and SBR (styrene-butadiene rubber) are selected as the binder, and copper foil or carbon-coated copper foil or porous copper foil is selected as the negative electrode current collector. The negative electrode active material, SP and binder are mixed in a ratio of 97:1:2, deionized water is added and stirred to form a uniform and stable negative electrode slurry. The negative electrode slurry is uniformly coated on the negative electrode current collector with a coating density of 110 g / m². 2 After drying and cold pressing, a positive electrode sheet is obtained, with a compaction density of 1.60 g / cm³. 3 .

[0143] 3. Separator membrane: PP (polypropylene) or PE (polyethylene) is selected as the base membrane for the separator membrane, with a thickness of 10μm.

[0144] 4. Cell assembly process: Arrange the positive electrode, separator, negative electrode, and separator in sequence, and use winding as the assembly method.

[0145] 5. Preparation of electrolyte: LiPF6 was dissolved in a solvent with a volume ratio of ethylene carbonate, methyl ethyl carbonate and diethyl carbonate of 1:1:1, and the concentration was 1.2 mol / L.

[0146] The electrolyte is injected into the dry cell and soaked for 10 hours. Then, it is formed at 45°C. The formation process is as follows: charge to 3.4V at 0.05C and then charge to 3.75V at 0.2C. The battery is manufactured after aging at room temperature for 24 hours.

[0147] Example 1

[0148] In Example 1, the preparation of the positive electrode sheet, negative electrode sheet, separator and electrolyte, as well as the assembly of the battery cell, are obtained by the above method. The protective layer in the positive electrode sheet includes 100 parts by mass of silicone rubber, 45 parts by mass of fumed silica, 40 parts by mass of aluminum hydroxide, and 2 parts by mass of bis(2,4)-dichlorosulfurizing agent.

[0149] Example 2

[0150] The difference in Example 2 is limited to the fact that the protective layer includes 100 parts by weight of silicone rubber, 47 parts by weight of fumed silica, 40 parts by weight of aluminum hydroxide, and 2 parts by weight of bis(2,4)-dichlorohydrin.

[0151] Example 3

[0152] The difference in Example 1 is limited to the fact that the protective layer includes 100 parts by weight of silicone rubber, 50 parts by weight of fumed silica, 40 parts by weight of aluminum hydroxide, and 2 parts by weight of bis(2,4)-dichlorohydrin.

[0153] Example 4

[0154] The difference between Example 4 and Example 1 is limited to the fact that the protective layer includes 100 parts by weight of silicone rubber, 50 parts by weight of fumed silica, 45 parts by weight of aluminum hydroxide, and 1.5 parts by weight of bis(2,4)-dichlorohydrin.

[0155] Example 5

[0156] The only difference between Example 5 and Example 1 is that the thickness of the protective layer is 10 μm.

[0157] Comparative Example 1

[0158] The only difference between Comparative Example 1 and Example 1 is that no protective layer is provided on the positive electrode of Comparative Example 1.

[0159] Comparative Example 2

[0160] The difference between Comparative Example 1 and Example 1 is limited to 1 part by weight of bis(2,4)-dichlorodimethylsulfide.

[0161] Performance testing

[0162] 1. Cyclic Test Procedure (Capacity Retention Rate after 1000 Cycles): Test temperature 25℃, 1C constant current discharge to 2.8V, rest for 30 minutes; then 1C constant current charge to 4.25V, followed by constant voltage discharge to the cutoff current of 0.05C, rest for 30 minutes, and then 1C constant current discharge to 2.8V. Record the discharge capacity at this point as the initial discharge capacity. This constitutes one charge-discharge cycle. Repeat this process until the discharge capacity decreases to 80% of the initial discharge capacity at SOC cutoff.

[0163] 2. Flexibility Test: Cut the electrode sheet to be tested into a suitable size, generally 5-10 cm in length and 1-2 cm in width, for easy operation and observation of the winding process. Gently hold the other end of the electrode sheet with your fingers and wind it around the steel needle at a uniform speed. Maintain uniform force during winding, avoiding sudden force or pauses, and try to make the electrode sheet adhere tightly to the steel needle. Start testing with a large-diameter steel needle, ranging from 5mm to 0.1mm in diameter, until cracks, breaks, or obvious delamination begin to appear on the electrode sheet. The steel needle one size larger than this diameter is the verification diameter, and the diameter of the steel needle indicates its flexibility.

[0164] 3. Operating Temperature Range Test: Set the target temperature of the high and low temperature chamber according to the test requirements. Once the chamber reaches the target temperature, place the sample (positive electrode sheet prepared in the example or comparative example) inside. The test time is 2-4 hours. After the specified test time, remove the sample and cool it to room temperature. Then observe the appearance changes of the sample, such as whether there is discoloration, cracks, blistering, delamination, etc. The electrode sheet should not crack. The test continues until the above failure phenomenon occurs, which is the boundary temperature of the protective layer. The test temperature ranges from -40℃ to 220℃, with each test point spaced 10℃ apart. Each test point uses a new electrode sheet for independent testing.

[0165] The test results of the above performance tests are shown in Table 1.

[0166] Table 1. Test Results:

[0167]

[0168] As shown in Table 1, compared to Comparative Examples 1-2, the protective coatings (protective layers) in Examples 1-5 help reduce side reactions between the electrode and the electrolyte, improve the cycle performance of the electrode, and the flame-retardant silicone rubber with good heat insulation properties can reduce the impact of heat diffusion on the electrode, thus improving the safety performance of the battery. Furthermore, it can also increase the operating temperature range of the electrode; in addition, the addition of the coating can improve the flexibility of the electrode and reduce damage to the electrode during processing.

[0169] In Comparative Example 1, the cycling performance decreased without the addition of a protective coating. In Comparative Example 1, the reduced crosslinking agent resulted in decreased mechanical strength and aging resistance of the protective coating, leading to its failure. As the cycle continued, the protective effect decreased. In Comparative Example 1, the first and second active materials of the positive electrode plate had already failed above 130°C.

[0170] The parts of this invention not described in detail are techniques known to those skilled in the art.

[0171] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.

[0172] It should be noted that the terms "and / or" or " / " used herein are merely descriptions of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The singular forms "a," "described," and "the" used in the embodiments of the invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0173] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.

[0174] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An electrode sheet, characterized in that, include: current collector; A first active material layer is disposed on at least one surface of the current collector, and the first active material layer includes a first active material. A second active material layer is disposed on the surface of the first active material layer away from the current collector, and the second active material layer includes a second active material. The first active substance and the second active substance are different; A protective layer is disposed on the surface of the second active material layer away from the first active material layer, and the protective layer comprises the following components in parts by weight: The mixture comprises 100 parts silicone rubber, 45-50 parts reinforcing agent, 40-45 parts flame retardant, and 1.5-2 parts vulcanizing agent; wherein the reinforcing agent includes at least one of sepiolite, zinc oxide, magnesium oxide, and fumed silica; the flame retardant includes at least one of magnesium hydroxide, aluminum hydroxide, and ammonium phosphate; and the vulcanizing agent includes bis(2,4)-dichlorosulfurizing agent. The thickness of the protective layer is 3μm to 10μm; the areal density of the protective layer is 15mg / m³. 2 ~30mg / m 2 .

2. The electrode sheet according to claim 1, characterized in that, The protective layer satisfies at least one of features (1) to (2): (1) The flame retardant includes at least one of aluminum hydroxide or magnesium hydroxide; (2) The reinforcing agent includes fumed silica.

3. The electrode sheet according to claim 1, characterized in that, The first active material and the second active material are positive electrode active materials, and the electrode sheet satisfies at least one of features (1) to (3): (1) The first active substance includes ternary material A; The ternary material A includes LiNi x Co y Mn 1-x-y O2 or LiNi x Co y Al 1-x-y At least one of O2; wherein x ≥ 0.8, 0.05 ≤ y ≤ 0.2; The ternary material A comprises primary particles; (2) The second active substance includes ternary material B; The ternary material B includes LiNi. x Co y Mn 1-x-y O2 or LiNi x Co y Al 1-x-y At least one of O2; wherein x ≥ 0.8, 0.05 ≤ y ≤ 0.2; The ternary material B comprises secondary particles; (3) Both the first active substance and the second active substance contain nickel, and the nickel content in the first active substance is different from that in the second active substance.

4. The electrode sheet according to claim 1, characterized in that, The first active material and the second active material are negative electrode active materials, and the electrode sheet satisfies at least one of features (1) to (4): (1) The first active material includes at least one of silicon-based materials and carbon-based materials; (2) The first active substance comprises primary particles; (3) The second active material includes at least one of silicon-based materials and carbon-based materials; (4) The second active substance includes secondary particles.

5. The electrode sheet according to any one of claims 1 to 4, characterized in that, The electrode satisfies at least one of features (1) to (4): (1) Based on the mass of the first active material layer, the mass percentage of the first active material is 95%~97%; (2) The first active material layer further includes a first conductive agent and a first binder; Based on the mass of the first active material layer, the mass percentage of the first conductive agent is 1% to 1.5%. Based on the mass of the first active material layer, the mass percentage of the first adhesive is 2% to 3.5%. The first conductive agent includes one or more of conductive carbon black, vapor-generated carbon fiber, graphene, or carbon nanotubes. (3) Based on the mass of the second active material layer, the mass percentage of the second active material is 95%~97%; (4) The second active material layer further includes a second conductive agent and a second binder; Based on the mass of the second active material layer, the mass percentage of the second conductive agent is 1% to 1.5%. Based on the mass of the second active material layer, the mass percentage of the second adhesive is 2% to 3.5%. The second conductive agent includes one or more of conductive carbon black, vapor-generated carbon fiber, graphene, or carbon nanotubes.

6. A method for preparing an electrode sheet as described in any one of claims 1 to 5, characterized in that, Includes the following steps: A first slurry is coated on at least one side of the current collector to obtain a first active material layer; A second slurry is coated on the surface of the first active material layer to obtain a second active material layer; A protective slurry is coated onto the surface of the second active material layer to obtain a protective layer. The first active material layer includes a first active material; the second active material layer includes a second active material; and the protective layer includes silicone rubber and additives.

7. The preparation method according to claim 6, characterized in that, The steps for obtaining the protective layer specifically include: The silicone rubber, flame retardant, reinforcing agent and vulcanizing agent are mixed evenly to obtain a protective slurry; The protective slurry is coated onto the surface of the second active material layer. The coating thickness is 10 μm to 40 μm. After drying, the protective layer is obtained.

8. A battery, characterized in that, include: The diaphragm, the electrolyte, and the electrode as described in any one of claims 1 to 5, and / or the electrode prepared by the preparation method described in any one of claims 6 to 7.

Citation Information

Patent Citations

  • Pole piece, preparation method of pole piece and battery

    CN111916645A

  • Secondary battery and electric device

    CN116314800A